2018
DOI: 10.1103/physrevb.97.184105
|View full text |Cite
|
Sign up to set email alerts
|

Structural transitions in hybrid improper ferroelectric Ca3Ti2O7 tuned by site-selective isovalent substitutions: A

Abstract: Ca3Ti2O7 is an experimentally confirmed hybrid improper ferroelectric material, in which the electric polarization is induced by a combination of the coherent TiO6 octahedral rotation and tilting. In this work, we investigate the tuning of ferroelectricity of Ca3Ti2O7 using iso-valent substitutions on Ca-sites. Due to the size mismatch, larger/smaller alkaline earths prefer A'/A sites respectively, allowing the possibility for site-selective substitutions.Without extra carriers, such site-selected iso-valent s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 27 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…The core-valence electron interaction was described using the projector augmented wave method 36 , and the exchange-correlation part was treated within the Perdew-Burke-Ernzerhof generalized gradient approximation 37 . The on-site Coulomb interaction (U eff ) of the Ti ions was set to 3 eV 38 . The cutoff energy for the plane-wave basis was 550 eV.…”
Section: Methodsmentioning
confidence: 99%
“…The core-valence electron interaction was described using the projector augmented wave method 36 , and the exchange-correlation part was treated within the Perdew-Burke-Ernzerhof generalized gradient approximation 37 . The on-site Coulomb interaction (U eff ) of the Ti ions was set to 3 eV 38 . The cutoff energy for the plane-wave basis was 550 eV.…”
Section: Methodsmentioning
confidence: 99%
“…(We refer to phases where dipole moments of each slab are zero as 'nonpolar'.) Many of these phases are observed to emerge in various A 3 B 2 O 7 oxides under biaxial strain or equivalent doping, and are also shown to be important as intermediate states in the coherent switching of polarization 5,16,[20][21][22]33 . This is in addition to single-tilt systems observed, for example, at finite temperature 7 .…”
Section: Review Of Crystal Structuresmentioning
confidence: 99%
“…reported that HIF was active in the layered perovskite oxides with the Ruddlesden–Popper (RP) structure and the chemical formula of (AO)­(ABO 3 ) n , n = 2, and recently predicted in n = 2 RP perovskite oxides (RPPOs) and chalcogenides (RPPCs), i . e ., Ca 3 Ti 2 O 7 , Sr 3 Sn 2 O 7 , Sr 3 Zr 2 O 7 , Ca 3 Zr 2 S 7 , Ca 3 Zr 2 Se 7 , Ca 3 Hf 2 S 7 , Ca 3 Hf 2 Se 7 , Sr 3 Zr 2 S 7 , and Sr 3 Hf 2 S 7 . , On the one hand, it is worth addressing that the HIF in RPPOs, i . e ., Ca 3 Ti 2 O 7 , Sr 3 Sn 2 O 7 , Sr 3 Zr 2 O 7 , and Ca 3 (Ti, Mn) 2 O 7 , was already experimentally confirmed. ,,, So far, all predicted HIF in RPPCs is still in the stage of theoretical predictions and in urgent need of experimental verification.…”
Section: Introductionmentioning
confidence: 99%